Flexural strength and reliability of monolithic and trilayer ceramic structures obtained by the CAD-on technique. Issue 12 (December 2015) - Basso, G.R.; Moraes, R.R.; Borba, M.; Griggs, J.A.; Della Bona, A.
Highlights: This study evaluates the flexural strength, Weibull modulus, and fracture mode of ceramic structures obtained by the CAD-on technique. This study tested the hypothesis that trilayer and monolithic structures show similar values for the evaluated properties. Monolithic and trilayer specimens showed similar mean flexural strengths, characteristic strengths and Weibull moduli. Considering the CAD-on technique, the trilayer structures showed greater fracture toughness than the monolithic zirconia specimens. Abstract: Objective: To evaluate the flexural strength, Weibull modulus, fracture toughness, and failure behavior of ceramic structures obtained by the CAD-on technique, testing the null hypothesis that trilayer structures show similar properties to monolithic structures. Methods: Bar-shaped (1.8 mm × 4 mm × 16 mm) monolithic specimens of zirconia (IPS e.max ZirCAD – Ivoclar Vivadent) and trilayer specimens of zirconia/fusion ceramic/lithium dissilicate (IPS e.max ZirCAD/IPS e.max CAD Crystall./Connect/IPS e.max CAD, Ivoclar Vivadent) were fabricated ( n  = 30). Specimens were tested in flexure in 37 °C deionized water using a universal testing machine at a crosshead speed of 0.5 mm/min. Failure loads were recorded, and the flexural strength values were calculated. Fractography principles were used to examine the fracture surfaces under optical and scanning electron microscopy. Data were statistically analyzed using Student's t -test and Weibull statistics ( α  = 0.05). Results: Monolithic and trilayer specimens showed similar mean flexural strengths, characteristic strengths, and Weibull moduli. Trilayer structures showed greater mean critical flaw and fracture toughness values than monolithic specimens ( p  < 0.001). Most critical flaws in the trilayer groups were located on the Y-TZP surface subjected to tension and propagated catastrophically. Trilayer structures showed no flaw deflection at the interface. Significance: Considering the CAD-on technique, the trilayer structures showed greater fracture toughness than the monolithic zirconia specimens.